Adverse drug reactions in Ghanaian children: review of reports from 2000 to 2012 in VigiBase - Cliff-Eribo, Kennedy Obebi; Choonara, Imti; Dodoo, Alex; Darko, Delese M.; Sammons, Helen (Taylor & Francis Group, 2015)
Objective: The aim of this article is to describe adverse drug reactions (ADRs) reported for children aged 0 - 17 years in Ghana. Methods: Paediatric reports submitted by the Ghana National Centre for Pharmacovigilance to the World Health Organisation (WHO) Global ADR database, VigiBase up to December 2012 were extracted. The data were analysed for number of reports per year, types of reporters and suspected ADRs and drugs. Results: A total of 343 reports for children were received during the period. The drug classes most frequently reported were vaccines (115, 31%), antimalarials (106, 28%) and antibiotics (57, 15%). Of the top 20 individual drugs, 19 were anti-infectives. The most frequently reported ADRs were injection site infection, fever and rash. There were 23 deaths reported, and antimalarials were implicated in 12 cases. Conclusions: Vaccines, antimalarials and antibiotics are the leading medicines reported to cause ADRs in Ghanaian children. There was a high mortality rate, with many of the deaths due to causes explained in the individual case safety reports.